MENINGKATKAN PENJUALAN PRODUK UMKM DENGAN MEMANFAATKAN MEDIA SOSIAL TIKTOK DAN APLIKASI CANVA - Santi Octavia; Daffa Naufal A; Selvia Pangestika; Syida Nurlaila; Iham Cahyadi; Sanggita Basungi; Aghni Azzironi; Ari Chadra D; Khaila Dzasha; Diah PS; Ningky Sasanti (Jurnal Abdimas Ekonomi dan Bisnis (JAmEB), 2023)
Technological developments have a significant impact on UMKM players. So, inevitably, UMKM players must adjust to marketing that used to be conventional and switch to online. Online sales are one of the right marketing strategies to use because more and more people are accessing the internet, one way to market products or sales via the internet is to market through social networks such as Facebook, Twitter, Instagram, tik-tok. The benefits of Community Development activities carried out at UMKM - Mutiara Depok Housing are in addition to providing assistance and socializing product marketing digitally with Tiktok Social-Media in increasing product sales and expanding market share by utilizing the Canva Application for branding product photos through digital marketing. Of the 12 UMKM players who participated in this activity, it shows that 80% of UMKM already have and utilize social media for their product marketing activities. As for those who have not used it because they do not understand its use, especially the Canva application